ASSESSING AND DEVELOPING PUBLIC LIBRARIES PERFORMANCE: KANO’S MODEL APPROACH - Taib, Che Azlan bin; Iteng, Rosman; Mad Lazim, Halim (International Journal of Supply Chain Management, 2018)
Perbadanan Perpustakaan Negeri Kedah (PPAK) was established in 1961. To determine whether the library is providing a good service has occupied the attention of PPAK management for many years. Thus, the library user survey has been conducted during the past few years. However, the study unable to place the correct position of library services. In order to determine in greater detail how the users perceived the various services offered by the PPAK, KANO model instrument was used. To achieve this objective, a set of questionnaire was prepared consisting of 50 items, and distributed to 500 respondents. Among these questionnaires, the valid numbers only 265 or 53%. Two hundred and thirty five was rejected because of filled out incompletely. At the first stage, the data were analyzed using Statistical Package for Social Science Package (SPSS). Then, the second stage Microsoft excel was employed to categorize the Kano s classification. The seven dimensions quality (easy to access, service is compatible, effectiveness of services, efficiency of services, service is reliable, provide right services, and the competency of staff) services taking from ALUS model were employed. Then, the users perception was analyzed and compared. Service quality requirements were classified into five Kano s classification attractive, must-be, one-dimensional, indifferent and questionable/reverse. The study found that PPAK service quality classified in Indifferent . Proposed for further research also discussed.